Patient Satisfaction with National Health Insurance and Public Health Center Accreditation: Lessons Learnt from Majalengka Regency, Indonesia - Ruhiyat, Yayat; Sunjaya, Deni Kurniadi; Gondodiputro, Sharon; Mutyara, Kuswandewi; Sujatmiko, Budi; Arisanti, Nita (Althea Medical Journal, 2023)
Background: Perceptions of patient satisfaction influence the quality of the public health center (Pusat Kesehatan Masyarakat, Puskesmas) services. This study aimed to determine the differences in the level of patient satisfaction with national health insurance and the accreditation status of Puskesmas.Methods: This quantitative analytical study using a cross-sectional method was conducted at four Puskesmas in Majalengka Regency from October to November 2021 using a purposive sampling technique. The instrument used was the community satisfaction instrument (IKM-29) questionnaire , with the variable measured being the level of satisfaction. Data was transformed into numerical form using Rasch modelling and analyzed using the Chi-Square, independent-t, and one-way ANOVA tests.Results: A total of 273 respondents consisted of insured (Jaminan Kesehatan Nasional, JKN) and non-insured (non-JKN) respondents, resulting in the satisfaction mean value between JKN and non-JKN patients of 2.50 and 2.51 (p-value= 0.926). Satisfaction at Puskesmas levels 1 (Dasar), 2 (Madya), 3 (Utama), and 4 (Paripurna) was 2.15, 2.23, 2.56, 3.03, respectively (p-value = 0.002), indicating an increase in the level of satisfaction at the Puskesmas accreditation level.Conclusion: There is no difference in satisfaction between respondents using JKN and non-JKN. However, there is an increase in satisfaction related to the Puskesmas accreditation level. It is recommended for each Puskesmas to maintain the same service to all patients and improve the quality of service, especially in service dimensions that are considered inferior. Additionally, it is necessary to review the minimum standard value for accreditation programs.